1999
DOI: 10.1093/ageing/28.6.537
|View full text |Cite
|
Sign up to set email alerts
|

The normal range for inter-arm differences in blood pressure

Abstract: the frequency of significant inter-arm systolic and diastolic blood pressure differences suggests that the blood pressure should be taken in both arms at the initial consultation. At subsequent visits, the arm in which measurements are taken should be recorded in the case notes. The higher of the two readings should be used to guide further management decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 6 publications
5
67
3
2
Order By: Relevance
“…4 However, the small difference in the magnitude of the absolute BPs between the right and left arms suggests that no systematic bias was introduced by this method, and this is in keeping with data from previously reported large series. 7,[20][21][22] Although there was good correlation of IADs between attendances, this study did not measure changes to the IAD over the follow-up period. Therefore, the impact of medication and risk factor modification on the IAD cannot be assessed.…”
Section: Discussionmentioning
confidence: 96%
“…4 However, the small difference in the magnitude of the absolute BPs between the right and left arms suggests that no systematic bias was introduced by this method, and this is in keeping with data from previously reported large series. 7,[20][21][22] Although there was good correlation of IADs between attendances, this study did not measure changes to the IAD over the follow-up period. Therefore, the impact of medication and risk factor modification on the IAD cannot be assessed.…”
Section: Discussionmentioning
confidence: 96%
“…[21][22][23][24][25]72 No study has set out to compare the prevalence of an IAD in patients with or without CHD; however, data extracted from one study meeting our inclusion criteria showed a significantly higher prevalence of sIADX10 mm Hg in patients with CVD than without (19.4 vs 2.7%; OR 4.34, 95% CI 2.09-9.04; Po0.0001). 52 Arteriosclerosis was also more common in subjects with an IAD in Kay and Gardner's study, 38 whereas although Singer and Hollander found no relationship between coronary risk factors and an IAD, they did find the mean sIAD to be significantly higher in patients with known coronary artery disease than without (14.5 vs 10.4 mm Hg; P ¼ 0.05). 55 Another smaller study reported higher prevalence of IAD in patients with PVD compared to both CHD patients and controls.…”
Section: Pathophysiology Of the Iadmentioning
confidence: 86%
“…[36][37][38][39][40][41] Studies looking specifically at left or right handedness have also failed to demonstrate an association with the higher-reading arm. 33,42 In the current study, blood pressures were recorded in a fixed sequence for anklebrachial index assessment, 18 which may account for the bias towards higher rightarm blood pressures observed through order effects.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%